Pre-accumulation and in-situ destruction of diclofenac by a photo-regenerable activated carbon fiber supported titanate nanotubes composite material: Intermediates, DFT calculation, and ecotoxicity - Dang, Chenyuan; Fengbin Sun; Jiang, Huan; Taobo Huang; Liu, Wen; Xingmin Chen; Ji, Haodong (Journal of Hazardous Materials, 2020)
Pharmaceuticals and personal care products (PPCPs) have been widely detected in ecosystems. However, effective water purification technologies for PPCPs degradation are lacking. In this work, an active activated carbon fiber supported titanate nanotubes (TNTs@ACF) composite was synthesized via one-step hydrothermal process, which was applied for adsorption and photocatalytic degradation of PPCPs under simulated solar light. Characterizations indicated that the successful grafting of TNTs onto ACF was achieved and surface modification occurred. Diclofenac (DCF, a model PPCPs) was rapidly adsorbed onto TNTs@ACF, and subsequently photodegraded (98.8 %) under solar light within 2 h. TNTs@ACF also performed well over a wide range of pH, and was resistant to humic acid. The good adsorption and photocatalytic activity of TNTs@ACF was attributed to the well-defined hybrid structure, enabling corporative adsorption of DCF by TNTs and ACF, and extending the light absorbance to visible region. Furthermore, the description of degradation pathway and evaluation of ecotoxicity for DCF and its intermediates/byproduct were proposed based on experimental analysis, density functional theory (DFT) calculation and quantitative structure–activity relationship (QSAR) analysis, respectively, indicating the photocatalytic degradation of DCF can offer the step-by-step de-toxicity. Our study is expected to offer new strategy as “pre-accumulation and in-situ destruction” for environmental application.
Keywords: Activated carbon fiber; Adsorption; Photo-regeneration; PPCPs; Titanate